Chapter Communicating safely & effectively using plant names - Allkin, Bob (Maven Publishers, 2014)
This paper describes a new initiative to provide information services in support of professionals, including legislators, that work in health, pharmacovigilance, the herbal and pharmaceutical industries or that undertake pharmaceutical research. The services are being designed to help these audiences to use plant names appropriately and navigate safely the rich information sources that already exist for medicinal plants. Input from the user community is sought to ensure that the services built meet practical needs and are sustainable.